The Need for Strengthening Health Information Dissemination Toward Indoor Residual Spraying for Malaria Prevention in Malarious Area of Ethiopia - Wubayehu Mekasha; Chala Daba; Asmamaw Malede; Sisay Abebe Debela; Mesfin Gebrehiwot (Frontiers in Public Health, 2022)
IntroductionMalaria remains prevalent in developing countries. This is particularly true among the community who are prone but do not apply malaria prevention and controlling strategies. In one of the malarious areas of Ethiopia (Shewa Robit), the acceptance level of indoor residual spraying (IRS) is indicated to be low as per guidelines. However, factors determining communities' acceptance of IRS are not well-investigated. Hence, this study was designed to identify the determinants for the acceptance of IRS in order to indicate priorities for malaria prevention and control.MethodsA community-based cross-sectional study design was used among 649 households in Shewa Robit town, from February to March 2021. Households were selected from five IRS-targeted kebeles. Data were collected using structured questionnaire. A multivariable logistic regression model was used to identify the independent factors associated with the acceptance of IRS.ResultsThe response rate in this study was 98%. The proportion of community who accepted the IRS for malaria prevention was 56.5% [95% confidence interval (CI): 52.7–60.2%]. Being male [adjusted odds ratio (AOR) = 2.21, 95% CI: 1.32–3.72], having good knowledge (AOR = 2.25, 95% CI: 1.33–3.84), did not paint/re-plaster the wall after spraying (AOR = 3.99, 95% CI: 2.36–6.76), did not perceive any side effects after spraying (AOR = 1.82, 95% CI: 1.11–2.99), effectiveness of previous IRS (AOR = 2.99, 95% CI: 1.85–4.84), non-utilization of long-lasting insecticide-treated net (LLIN) (AOR = 0.52, 95% CI: 0.33–0.84), and spraying the house at the right season (AOR: 2.14, 95% CI: 1.11–4.13) were determinant factors for the acceptance of IRS.ConclusionsTo increase the acceptance level of IRS among the communities, health interventions and services should focus on the awareness creation toward the effectiveness of IRS, proper spraying time/season, and side effects of IRS. Therefore, strengthening health information dissemination could help promote the acceptance of IRS.